A Pharmacokinetic Evaluation of a Pectin-Based Oral Multiparticulate Matrix Carrier of Carbamazepine - Seth Kwabena Amponsah; Simon Yeboah; Kennedy Kwami Edem Kukuia; Benoit Banga N'guessan; Ofosua Adi-Dako (Hindawi Limited, 2021)
Background. Carbamazepine is a drug used in the treatment of neurological disorders such as epilepsy. However, due to its erratic absorption, oral bioavailability is often poor. There is, therefore, the need to develop alternative formulations for carbamazepine with better pharmacokinetic characteristics. Aim. The aim of this study was to formulate an oral modified-release multiparticulate matrix of carbamazepine from cocoa pod husk (CPH) pectin and evaluate the pharmacokinetic profile of this formulation using in vitro and in vivo models. Methods. CPH pectin was extracted from cocoa pod husks with hot aqueous and citric acid solutions. Oral multiparticulate carbamazepine matrices were formulated from CPH pectin cross-linked with calcium. The formulation was evaluated for carbamazepine content and release profile in vitro. For in vivo pharmacokinetic profile estimation, rats were put into 4 groups of 5 animals each to receive carbamazepine multiparticulate matrix formulations A and B, carbamazepine powder, and Tegretol CR®. Animals in each group received 200 mg/kg of each drug via the oral route. Maximum plasma concentration Cmax, area under the concentration-time curve (AUC), elimination rate constant Ke, and terminal half-life t1/2 of the formulations were estimated by noncompartmental analysis. Results. The pectin extraction from fresh cocoa pod husks using hot aqueous and citric acid solutions gave pectin yields of 9.63% and 11.54%, respectively. The drug content of carbamazepine in CPH pectin formulations A and B was 95% and 96%, respectively. There was controlled and sustained release of carbamazepine for both formulations A and B in vitro. AUC0⟶36 (176.20 ± 7.97 µg.h/mL), Cmax (8.45 ± 0.71 μg/mL), Tmax (12 ± 1.28 h), and t1/2 (13.75 ± 3.28 h) of formulation A showed a moderately enhanced and comparable pharmacokinetic profile to Tegretol CR® (AUC0⟶36: 155 ± 7.15 µg.h/mL, Cmax: 8.24 ± 0.45 μg/mL, Tmax: 8.0 ± 2.23 h, and t1/2: 13.51 ± 2.87 h). Conclusion. Findings from the study suggest that formulations of CPH pectin had the potential to control and maintain therapeutic concentrations of carbamazepine in circulation over a period of time in the rat model.